New potent steroid sulphatase inhibitors based on 6-(1-phenyl-1H-1, 2, 3-triazol-4-yl)naphthalen-2-yl sulphamate derivatives. (1st January 2021) - Ciupak, Olga; Daśko, Mateusz; Biernacki, Karol; Rachon, Janusz; Masłyk, Maciej; Kubiński, Konrad; Martyna, Aleksandra; Demkowicz, Sebastian
Abstract: In the present work, we report a new class of potent steroid sulphatase (STS) inhibitors based on 6-(1-phenyl-1 H -1, 2, 3-triazol-4-yl)naphthalen-2-yl sulphamate derivatives. Within the set of new STS inhibitors, 6-(1-(1, 2, 3-trifluorophenyl)-1 H -1, 2, 3-triazol-4-yl)naphthalen-2-yl sulphamate 3L demonstrated the highest activity in the enzymatic assay inhibiting the STS activity to 7.98% at 0.5 µM concentration. Furthermore, to verify whether the obtained STS inhibitors are able to pass through the cellular membrane effectively, cell line experiments have been carried out. We found that the lowest STS activities were measured in the presence of compound 3L (remaining STS activity of 5.22%, 27.48% and 99.0% at 100, 10 and 1 nM concentrations, respectively). The measured STS activities for Irosustat (used as a reference) were 5.72%, 12.93% and 16.83% in the same concentration range. Moreover, a determined IC50 value of 15.97 nM for 3L showed that this compound is a very promising candidate for further preclinical investigations.